Milk manufacture in Ukraine: current state, main trends of development and problems - Bogdaniuk, O. V.; Kostiuk, A. O. (НУБіП України, 2018)
Negative trends in the development of the livestock sector in Ukraine: reducing the number of animals, reducing milk production and reducing its qualitative indicators, require an in-depth study of the current state of the industry and the reasons for the decline in production, as well as the prospects of the industry according to the latest changes in the legislation of Ukraine. The main purpose of writing the article is to highlight the current state of one of the most important sectors of agricultural production in Ukraine - animal husbandry. The in-depth study covers the main issues and peculiarities of the development of dairy production in Ukraine. According to the results of the study, the recommendations and ways to increase milk production and increase its quality were given.
Виробництвo молока в Україні: сучасний стан, основні тенденції розвитку та проблеми
Негативні тенденції в розвитку галузі тваринництва України: скорочення поголів’я тварин, зменшення обсягу виробництва молока й зниження його якісних показників потребують поглибленого дослідження сучасного стану галузі та причин зменшення виробництва, а також розгляду перспективи галузі згідно з останніми змінами в законодавстві України. Метою написання статті є висвітлення сучасного стану однієї з найважливіших галузей сільськогосподарського виробництва України - тваринництва. Поглиблене дослідження охоплює основні питання та особливості розвитку молочного виробництва в Україні. За результатами проведеного дослідження надано рекомендації та шляхи щодо збільшення виробництва молока й підвищення його якості
Keywords: молоко; продуктивність тварин; milk; animal productivity; livestock numbers